EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY DENGAN PENDEKATAN MATEMATIKA REALISTIK PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI AKTIVITAS BELAJAR SISWA SMP KELAS VIII DI KABUPATEN SLEMAN TAHUN PELAJARAN 2013/2014 - Saputra, Very Hendra; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The objective of this research was to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the learning activity of the students. This research used the quasi experimental research with the factorial design of 3x3. Its population was all of the students in Grade VIII of State Junior Secondary Schools of Sleman Regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique and consisted of 254 students. Balance test used one way ANOVA test. The prerequisite test of the research included normality test with Lilliefors’ method and homogeneity test with Bartlett’s method of Chi Square test. With the significance level of α = 0.05. The data was analyzed by using the two way analysis of variance with unbalanced cells. The results of the research are as follows: 1) the Two Stay Two Stray learning model results in the same good learning achievement in Mathematics as the direct learning model, and the Two Stay Two Stray with Realistic Mathematics Approach learning model results in a better than the Two Stay Two Stray learning model and direct learning model, 2) the students with the high learning activity have a better learning achievement in Mathematics than those with moderate and low learning activities, and the students with the moderate learning activity have a better learning achievement in Mathematics than those with the low learning activity, 3) there is an intereaction the aforementioned learning models and the categories of the learning activity on the learning achievement in Mathematics of the student.Keyword: Realistic Mathematics Approach, Two Stay Two Stray (TS-TS), Learning Activity